Difficulties experienced by new international entrepreneurs in North-Karelia. - Nguyen, Bao Nhi (2021)
Along with the development of the world economy, there is presently an increasing number of entrepreneurs; even they are still students. Many immigrant entrepreneurs now like starting a new business in foreign countries. This research focuses on common difficulties immigrant entrepreneurs must encounter in Finland and solutions to overcome these difficulties. Furthermore, the study also explores immigrant entrepreneurs’ motivation when starting a new business in Finland. Qualitative research is adopted in this research. The subjects of this research are a business advisor and a Karelia UAS entrepreneur student. Data is collected from them through a semi-structured interview as the only instrument of the research. The findings revealed that immigrant entrepreneurs’ motivations to start a new business in Finland are to help other people make profits and easy to start a business in Finland. Moreover, Finland has many good conditions for immigrant entrepreneurs to develop their businesses. The results showed some difficulties of immigrant entrepreneurs are lack of experience, funds and language and cultural knowledge. To overcome these difficulties, the respondents stated that immigrant entrepreneurs could improve their language, culture, experience. They can also get support from organizations. Based on the results, some advice and suggested support services are recommended.